Total synthesis of (+)-petromyroxol via tandem alpha-aminoxylation-allylation and asymmetric dihydroxylation-S(N)2 cyclization approach - Nookaraju, U.; Kumar, Pradeep (RSC Advances, 2015)
The total synthesis of (+)-petromyroxol, a tetrahydrofuran (THF)-diol fatty acid, isolated from sea lamprey larvae (Petromyzon marinus) is reported. The present synthesis employs a tandem alpha-aminoxylationallylation, cross metathesis and tandem asymmetric dihydroxylation-S(N)2 cyclization as key steps.

Tetrahydrofuran ring construction through tandem iodocyclizations: synthesis of hagen's gland lactones, a pheromone of idea leuconoe , an oxylipid, and related compounds - Nookaraju, U.; Danve, Shivam S.; Kumar, Pradeep (Synlett, 2025)
A simple and efficient common route was developed for the syntheses of tetrahydrofuran-ring-containing natural products such as Hagen's gland lactones and their epimers, a pheromone of the butterfly Idea leuconoe, an oxylipid, and some valuable synthons. Brown's allylation, cross-metathesis, iodocyclization, and a tandem aminoxylation/allylation were employed as key steps in the syntheses.
Keywords: Cross-metathesis; Hagen's gland lactone; Iodocyclization; oxylipids; pheromones; tetrahydrofurans